Abhängigkeit des Versuchsergebnisses bei der Termitenprüfung von der Prüfdauer (Isoptera). - Schultze-Dewitz, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1965)
Tests were made with sapwood and heartwood of Scots pine (Pinus silvestris) and Douglas fir (Pseudotsuga taxifolia) during four different test periods, using 200 workers of the subterranean termite Reticulitermes lucifugus Rossi. The most conclusive results were gained after 8 weeks, but it appeared that the results of a test period of 4 or 6 weeks were quite sufficient for tests of wood, wood products and other materials. For tests of wood preservatives the same method can be used. Apart from other results, the test showed that untreated sapwood of Douglas fir was more resistent even after 8 years of storage than heartwood was at the beginning. This difference seems to disappear after one month of attack by the wood-destroying fungus Coniophora cerebella (Pers.) Duby, as evidenced by the subsequent termite test. The influence of the test arrangement on the result is greater than that of the duration of the test.